Long-Term Compliance with Continuous Positive Airway Pressure in Patients with Obstructive Sleep Apnea - Norman Wolkove; Marc Baltzan; Hany Kamel; Richard Dabrusin; Mark Palayew (Canadian Respiratory Journal)
BACKGROUND: Continuous positive airway pressure (CPAP) is an effective treatment for obstructive sleep apnea (OSA). However, compliance is a significant problem and has been incompletely assessed in long-term studies.